Efek Biokonversi Pulp Kakao menjadi Bioetanol Sebagai Sumber Energi Alternatif melalui Fermentasi Aspergillus niger dan Saccharomyces cerevisiae dalam Fermentor Wadah Plastik dan Stainless Steel - Desi Riana Saputri; Fenzy Putri Liewenti; Stanislaus Dimas Indra (Journal of Science and Applicative Technology, 2021)
Cocoa beans from Indonesian farmers are not optimal to utilize dan has low quality because they have not done fermentation processing. The aim of this study was to process cocoa beans through fermentation by using Aspergillus niger and Saccharomyces cerevisiae by developing cocoa-pulp byproduct that can be converted to be alcohol. Fermentation process had done in two type of containers such as plastic and stainless steel material. It was observed to know the presence of olygodinamic effect from stainless steel material. The results showed that cacao pulp can be fermented by using Aspergillus niger and Saccharomyces cerevisiae in sensory test method with hyphae growth and strong aromatic from alcohol observation. Stainless steel material in fermentor tub did not give the oligodynamic effect for Aspergillus niger fungus and Saccharomyces cerevisiae growth. The Fermentation process produced 0.66 mL of alcohol from one kilogram fresh cocoa beans. The maximum bioethanol product is that happened in 4th day fermentation process about 5.30 %.